CHANGES IN BODY COMPOSITION AND PERFORMANCE OF A CEREBRAL PALSY PARALYMPIC ATHLETE IN PREPARATION FOR THE LONDON PARALYMPIC GAMES. Issue 17 (24th October 2013) - Shreeve, S; Rowley, N; Gilby, C; Mitchell, N
Abstract : This case study examined body composition changes of a cerebral palsy (CP) athlete, in the 12 weeks prior to the London 2012 Paralympic Games. The aim was to monitor body composition of an athlete in preparation for the London Paralympic Games as part of the optimisation of performance. Within a 12 week period, body composition assessments were completed alongside an incremental 7×200 m swimming performance test, each separated by 6 weeks. One ISAK trained anthropometrist recorded body mass, sum of 8 skinfold thicknesses (biceps, triceps, subscapular, iliac crest, supraspinale, abdominal, front thigh and medial calf), girths (arm, waist, hips and calf), alongside calculations of mid upper arm muscle circumference (MUAMC). With the athlete's non-affected side being the left side, additional measurements of arm and calf circumference, bicep and triceps skinfold and MUAMC were also assessed. Sum of 8 skinfolds fluctuated over weeks 1, 6 and 12 with 65.8 mm, 60.7 mm and 63.0 mm respectively. Arm circumference in the dominant left arm increased in the 12 week period 29.7 cm, 29.4 cm and 30.5 cm respectively, with the non-dominant right arm maintaining arm circumference over the same period. Performance in the final 200 m of the incremental performance test improved at each time point. 1.2% improvement in performance was noted between weeks 1 and 6 and a 2.1% improvement between weeks 6 and 12. A total performance improvement of 3.2% was noted from the start to end of the 12 week period. This case study highlights in a CP athlete, performance and body composition changes in the lead into major competition. There was little change in body composition but improvements in performance. This suggests that minimal body fat is not critical in CP swimming performance. However, the athlete maintained muscle mass which may suggest that functional mass is more an indicator of performance and provides a direction for future work.